RELATIONSHIP ATTITUDE AND GOVERNMENT COMMITMENT COMPLIANCE WITH THE IMPLEMENTATION OF THE COVID-19 HEALTH PROTOCOL IN JAMBI CITY TOURISM PLACES - Putri, Fitria Eka; Ningsih, Vinna Rahayu; Yuliana, Yuliana; Hubaybah, Hubaybah; Fitri, Adelina; Hidayati, Fajrina (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2023)
Background: Tourist attractions have the potential to become a locus of spread of COVID-19 if there is a gathering of visitors while traveling causing compliance with the implementation of health protocols to break the chain of transmission of COVID-19. The emergence of the term Revenge Tourism or revenge tourism after the implementation of the new normal, where during the Covid-19 pandemic made many people experience boredom in the midst of social implementation so walking is a way to reduce boredom and boredom while implementing the house.Objective: This study aims to look at the relationship between the government's attitude and commitment to compliance and implementation of the Covid-19 health protocol in tourist attractions in Jambi City.Methods: This type of research is observational with a cross-sectional design. This research was conducted at tourist attractions in the city of Jambi in June-August 2022. The population in this study were 378 visitors to tourist attractions.Results: Based on the research results obtained, the majority of respondents had a positive attitude about implementing health protocols during the Covid-19 pandemic at tourist attractions, namely 191 respondents (50.5%), then most of them had the government's commitment to preventing Covid-19 in tourist attractions, namely as many as 237 respondents (67.2%) statistical test there is a significant relationship between attitudes (p=0.000) and government commitment (p=0.000) with adherence to the implementation of health protocols during the Covid-19 pandemic in tourist attractions Jambi city.Conclusion: There is a significant relationship between attitude (p=0.000) and government commitment (p=0.000) with adherence to the implementation of health protocols during the Covid-19 pandemic in Jambi city tourist attractionsKeyword: Covid-19, Health Protocols, Tourist spots